Gomorrah - Matteo Garrone (2008)
Power, money and blood: these are the values that the residents of the province of Naples and Caserta confront every day. They have practically no choice, and are forced to obey the rules of the "System," the Camorra. Only a lucky few can even think of leading a normal life. Five stories are woven together in this violent scenario, set in a cruel and ostensibly invented world, but one that is deeply rooted in reality.
Keywords: Crime, Drama